2006
DOI: 10.1111/j.1537-2995.2006.00941.x
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania: risk to the blood supply

Abstract: Leishmania infection is most often transmitted to humans via the bite of the phlebotomine sandfly, but transmission of Leishmania by transfusion has also been reported. There has been a huge increase in the incidence of cutaneous and visceral leishmaniasis in Iraq and Afghanistan. The deployment of US troops to these countries and published case reports of transmission to soldiers in endemic areas, by transfusion to infants with immature immune systems, and to individuals immunocompromised by disease or immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 39 publications
(71 reference statements)
1
67
0
5
Order By: Relevance
“…It has been shown that Leishmania can circulate in asymptomatic blood donors more than 1 year after exposure (Fichoux et al 1999;Cardo 2006). Therefore there is a risk of transmission of Leishmania to blood recipients due to its subclinical persistence in infected individuals.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that Leishmania can circulate in asymptomatic blood donors more than 1 year after exposure (Fichoux et al 1999;Cardo 2006). Therefore there is a risk of transmission of Leishmania to blood recipients due to its subclinical persistence in infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of Leishmania through transfusion requires parasites to be present in the blood, either within infected white blood cells, or as free amastigotes released from phagocytes (Cardo 2006). Furthermore, the parasite should survive during processing and storage of blood.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations